Pengaruh Pendidikan Kesehatan Tentang Higiene Menstruasi Terhadap Pengetahuan Remaja Putri - Dolang, Mariene Wiwin; Kiriwenno, Erlin (INSTITUT AGAMA ISLAM NEGERI AMBON, 2020)
This study discusses the importance of health education about menstrual hygiene to the knowledge of young women. This research is a Pre Experiment research by designing One Group Pratt Posttest. The sample in this study were 35 male students of SMP Negeri 1 masohi who had menstruated. Data processing and analysis is done by computerization and presented in the form of frequency distribution and cross tabulation by using the Indepentent T Test if the data is normally distributed and if the data is not normally distributed the Wilcoxon test is used with a significance level of p